EFFECT LEADERSHIP STYLE HEAD MASTER OF THE TEACHER PERFORMANCE ELEMANTARI SCHOOL NO 07 DISTRICT PONTIANAK CITY - B31112127, Siti Nurhasanah (Jurnal Manajemen Update, 2016)
Schools as a formal educational institutionsthat aimed at shaping the human personality, in developing the intellectual learners in order to achieve the life of the nation. The principal as a leader role is very important to help teachers to improve the quality of education, a school principal should be able to improve the performance of teachers or the subordinate. Given the importance of the role of a leader in supporting the accomplishment of it, authors are encouraged to conduct research on leadership style Headmaster of the Teacher Performance SDN 07 district Pontianak City. The purpose of this study was to examine and analyze the effect Otokritas leadership style, leadership of the Liberal and leadership of the Demoktaris to performance of teachers at SDN 07 district Pontianak City. In this study, the population was all teachers at SDN 07 district. Pontianak City as many as 30 people but does not include the principal. Methods of data collection are using questionnaires, interviews and document methods while the techniques of sampling is using census techniques. The analytical method used in this research is descriptive and Causality. The results of this study can be concluded that variable autocratic leadership style, democratic and liberal simultaneously does not affect to performance of the State Primary School Teachers 07 District of Pontianak City. While partially independent variables autocratic leadership style, democratic and liberal does not have any significant effect on fixed variable then Ho is accepted and Ha rejected. Â  Keywords: Leadership Style, Principal and Teacher Performance